Defect Detection Equalization Of Hard Disk Drive Media Test Process Using Variable Bias Implementation In Touch Down Sensor Response - Ramachandran, Ganesalingam (2017)
The drive to satisfy the ever increasing need for digital storage capacity today has brought about various advances from a technological stand point in the design and manufacture of high speed and high capacity hard disk drives. Efforts to increase the areal density of the magnetic media disk within the hard disk drive forced designers to push the envelope of the read/write head’s flying height clearance using Thermal or Dynamic Fly Height Control (DFH) down to the sub–nanometer region, thus giving birth to the need for improved magnetic media disk manufacturing processes. In order to fly the heads ever closer to the magnetic media surface, the media needed to be free of any protrusion or asperity type defects that could prove fatal to the drive, which in turn, was achieved through the use of the Touch Down Sensor. This research paper aims to address the variation that is present within the Touch Down Sensor application that employs the fixed bias implementation in the magnetic media test environment through the use of a variable bias solution. The amplitude response variation within the current implementation is scrutinized, and an alternative technique using a variable bias solution that is derived using an extrapolation of the amplitude response curve is discussed. The variable bias solution demonstrated that the variation of the Touch Down Sensor could be significantly be reduced by 36.7% and established a foundation where future research into this implementation could be explored